2017
DOI: 10.1016/j.jpor.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sleep bruxism with a novel designed occlusal splint

Abstract: From our results, it is suggested that we are not able to eliminate the influence of parafunction for the prosthesis only by designing the surface of occlusal splint using the semi-adjustable articulator. Our splint may have the potential to detect specific facets due to parafunctions as nocturnal bruxism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 14 publications
4
33
0
Order By: Relevance
“…This system could observe not only the surface loss but also the warp deformation of the splint by scanning the splint made of a specific elastic material on the cast. 37 In the current study, Geomagic Control X and Geomagic Studio was used to calculate the depth and volume losses for both kinds of splints. This method was first described by Mehl et al 38 and has been proven to be an appropriate way of assessing clinical wear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This system could observe not only the surface loss but also the warp deformation of the splint by scanning the splint made of a specific elastic material on the cast. 37 In the current study, Geomagic Control X and Geomagic Studio was used to calculate the depth and volume losses for both kinds of splints. This method was first described by Mehl et al 38 and has been proven to be an appropriate way of assessing clinical wear.…”
Section: Discussionmentioning
confidence: 99%
“…For occlusal splints, Kentaro proposed an evaluation system which can analyse the location and direction of wear facets and surface loss. This system could observe not only the surface loss but also the warp deformation of the splint by scanning the splint made of a specific elastic material on the cast 37 . In the current study, Geomagic Control X and Geomagic Studio was used to calculate the depth and volume losses for both kinds of splints.…”
Section: Discussionmentioning
confidence: 99%
“…Scratching in the friction direction is an evidence of abrasion wear of polymers [56]. Observations, terminology and definitions contained in the papers [32,55,56], as well as others, incl. [57], are the most appropriate in relation to scratch damage of polymers used to orthodontic appliances.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers found that deformation and abrasion were observed where human teeth contacted polymeric orthodontic appliances. It was shown that the degree of damage to orthodonic appliances was correlated with maximum muscle activity during sleep [32]. Such damage limits the effect of treatment and the durability of medical devices.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main challenges of dentistry is to identify whether the patient presents bruxism in the daytime or nighttime according to his report of myofascial pain [ 4 ]. Sleep bruxism is a common chronic condition in approximately 8% of the population [ 7 ] and, if improperly diagnosed or untreated, it can cause considerable damage to the teeth; the repair is complex [ 8 ]. According to a recent review, both types of bruxism, both physiological and pathological, have associated causal factors that are yet unknown.…”
Section: Introductionmentioning
confidence: 99%